A modified protocol for isolation of retinal microglia from the pig. (June 2021) - Zhang, Yahan; Erhard, Anna Lena; Plagemann, Tanja; Eter, Nicole; Heiduschka, Peter
Abstract: Microglia are the resident immune cells in the retina. To investigate their properties and behaviour, a reliable and yielding procedure to culture them is necessary. We here describe a way of isolation of microglial cells from the porcine retina, as pig eyes are similar to human eyes in size, structure and vasculature, including similarities in proteins and pathways. Retina was isolated from fresh pig eyes, dissociated by a mixture of collagenase, hyaluronidase and DNAse, and passed through a cell strainer. After triple centrifugation with decreasing velocity and re-suspension, cells were seeded into poly-d -lysine coated culture flasks and cultured using DMEM and macrophage-colony stimulating factor (M-CSF). Number of cells increased gradually during the first 10–14 days, till they could be split and used for experiments. Identity of isolated cells as microglia was assessed by immunostaining against the microglia/macrophage markers Iba1, CD11b, CD68, CD45 and TMEM119. Phagocytic function of microglia could be demonstrated by phagocytosis of fluorescence beads and their response to lipopolysaccharide (LPS). As a conclusion, we developed a protocol for isolation and cultivation of pig retinal microglial cells that are suitable for research in the laboratory.